Pollution levels and deposition processes of airborne organic pollutants over the central Adriatic area: Temporal variabilities and source identification. (November 2021) - Jakovljević, Ivana; Šimić, Iva; Mendaš, Gordana; Sever Štrukil, Zdravka; Žužul, Silva; Gluščić, Valentina; Godec, Ranka; Pehnec, Gordana; Bešlić, Ivan; Milinković, Andrea; Bakija Alempijević, Saranda; Šala, Martin; et al.
Abstract: First data on polycyclic aromatic hydrocarbons (PAHs) and nitro-aromatic compounds (NACs) in aerosols as well as of PAHs, polychlorinated biphenyls (PCBs) and NACs in bulk and wet atmospheric deposition samples were simultaneously obtained during 6-month-long field campaign at the costal central Adriatic area. Special attention was given to open-fire biomass burning episodes as extreme events common for the overall Mediterranean coastal area in order to gain a better understanding of the atmospheric variabilities and potential sources of trace organic pollutants in coastal environments. Diesel and gasoline combustion related to land and maritime traffic as well as occasional open-fire episodes (forest fires) were found to be the dominant pollution sources of PAHs in PM10 particles. NACs were determined almost exclusively in samples affected by biomass burning episodes. Open-fire episodes had a strong contribution to the overall NACs atmospheric deposition fluxes. Several chlorinated congeners of PCBs were predominantly contributed in deposition samples. Highlights: First data of organic contents in aerosols and deposition samples at the Adriatic area Data obtained during biomass burning events as extreme events for the Adriatic area Strong influence of biomass burning on deposition fluxes of organic contents